Reforms for women : future options - Heptulla, Najma, 1940- (New Delhi : Oxford & IBH Pub. Co., 1992)
Papers presented at a seminar organized on Aug. 21, 1991 in New Delhi, India.
Includes bibliographical references.
Keywords: Women -- India -- Congresses